2015
DOI: 10.1155/2015/350829
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectral Characterization, and Biochemical Evaluation of Antidiabetic Properties of a New Zinc-Diosmin Complex Studied in High Fat Diet Fed-Low Dose Streptozotocin Induced Experimental Type 2 Diabetes in Rats

Abstract: In view of the established antidiabetic properties of zinc, the present study was aimed at evaluating the hypoglycemic properties of a new zinc-diosmin complex in high fat diet fed-low dose streptozotocin induced experimental type 2 diabetes in rats. Zinc-diosmin complex was synthesized and characterized by various spectral studies. The complexation between zinc ions and diosmin was further evidenced by pH-potentiometric titrations and Job's plot. Diabetic rats were orally treated with zinc-diosmin complex at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 71 publications
0
18
2
Order By: Relevance
“…Previous research has demonstrated that chronic diosmin treatment significantly increased plasma insulin and improved diabetic symptoms in STZ‐NA‐induced diabetic rats . In HFD‐STZ induced type 2 diabetic rats, oral administration of zinc‐diosmin complex leads to improve insulin secretion . However, in the present study, the plasma insulin level was not influenced by diosmin, even at the highest dose in STZ‐diabetic rats.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Previous research has demonstrated that chronic diosmin treatment significantly increased plasma insulin and improved diabetic symptoms in STZ‐NA‐induced diabetic rats . In HFD‐STZ induced type 2 diabetic rats, oral administration of zinc‐diosmin complex leads to improve insulin secretion . However, in the present study, the plasma insulin level was not influenced by diosmin, even at the highest dose in STZ‐diabetic rats.…”
Section: Discussioncontrasting
confidence: 76%
“…6,11 In HFD-STZ induced type 2 diabetic rats, oral administration of zinc-diosmin complex leads to improve insulin secretion. 12 However, in the present study, the plasma insulin level was not influenced by diosmin, even at the highest dose in STZ-diabetic rats. Therefore, the hypoglycaemic action of diosmin in STZ-induced type 1 diabetes rats seems not to be associated with the endogenous insulin.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Ever since in 1980, Coulston and Dandona reported the insulin mimetic activity of zinc ions, several research groups developed insulin mimetic zinc complexes with various coordination modes around zinc (II) ion and evaluated its glucose normalizing effect [14]. In the recent past, we have synthesized several new zinc complexes such as zinc-flavonol [15], zinc-morin [16], zinc-silibinin [17], zinc-diosmin [18] and evaluated for its toxicity as well as pharmacological properties in high-fat diet (HFD) fed -low-dose streptozotocin (STZ)-induced experimental T2D in rats. In the light of knowledge and expertise gained, in the present study an attempt has been made to synthesize a new metformin-zinc-flavonol complex and biochemically evaluated its toxicity as well as antidiabetic properties.…”
Section: Introductionmentioning
confidence: 99%